TECHNETIUM-99M MIBI GATED MYOCARDIAL PERFUSION SINGLE PHOTON EMISSION COMPUTED TOMOGRAPHY IMAGING – VALIDATION OF STRESS ONLY PROTOCOL - Dar, Zaigham Salim; Raza, Mehdi; Atif, Muhammad; Bukhari, Aown Raza (Pakistan Armed Forces Medical Journal, 2021)
Objective: To validate ‘stress only’ protocol against ‘rest stress protocol in normal and essentially normal cases undergoing Tc99m MIBI gated myocardial perfusion Single Photon Emission Computed Tomography imaging. Study Design: A retrospective observational study. Place and Duration of Study: Department of Nuclear Cardiology, Armed Forces Institute of Cardiology/National Institute of Heart Disease, Rawalpindi, Pakistan, from Jul to Sep 2019. Methodology: 136 cases were included. Patients underwent Tc-99m gated Single Photon Emission Computed Tomography MPI using a single day, rest/stress protocol. The rest study was performed first with 8-10 mCi Tc-99m MIBI followed by stress study, 3 hours later with 3 times the rest dose. The most common stress technique was pharmacological stress and bicycle ergometer exercise with 0.14 mg/kg/min adenosine infusion. Few patients underwent physical stress using Bruce protocol, achieving a minimum of 85% of the target heart rate. Mages–stress followed by rest–were evaluated by two experienced nuclear cardiologists (blinded to the MPI reports) and interpreted as ‘normal’ or ‘essentially normal’. Results: Evaluation of stress-only and rest-stress Single Photon Emission Computed Tomography myocardial images yielded a concordance rate of 84.56% with Cohen’s kappa coefficient of 0.69. Conclusion: Substantial agreement and good concordance were found in normal and essentially normal ‘stress only’ and ‘rest stress protocols.